Introducción al sistema VAX-11 780 y operación y administración del sistema VAX VMS - Jallath Coria, Eduardo S.; Muñíz Zafra, Sócrates A.; Sánchez Sandoval, Humberto; Jiménez García, Alejandro (My University, 1985)
As an operator, you must become proficient with the DCL commands that control and interact with images, processes, and VMS itself. There are DCL commands that can be used to modify your DCL environment. These commands make easier to use and you, as on operator, more efficient. One method of changing your DCL environment is trough what are known as command procedure files As an operator, you must become proficient with the DCL commands that control and interact with images, processes, and VMS itself.. Command procedure file contain a series of DCL commands. VMS can read the DCL commands from the files instead of from your terminal by placing commonly-used DCL command sequences in these files, a user can more easily interact with VMS.
Keywords: syntax; specifications; modifyng; floppies; duties